Fatty Acid and Sterol Compositions of Hatay Olive Oils - Dilsat Bozdogan Konuskan (Turkish Journal of Agriculture: Food Science and Technology)
In this study, sterol and fatty acid compositions with the other quality criteria (free fatty acids, peroxide value, total chlorophyll and carotenoid content) of olive oil samples obtained from Halhalı, Gemlik and Sarı Hasebi varieties through two phase mechanical method (crushing, kneading and centrifuge) was determined. Oleic, palmitic, linoleic, stearic, palmitoleic, linolenic and arachidic acids were the determined as the main fatty acids in olive oil samples. It was determined that oleic acid contents of oil samples ranged between 66.25-76.14% and Sarı Hasebi had the highest oleic acid content. Sterol and fatty acid compositions of olive oil samples showed significantly statistical differences according to varieties. It was determined that the total sterol contents of oils ranged between 1025 and 1686 mg/kg and varieties with the highest and lowest total sterol content were Gemlik and Sarı Hasebi. Apparent β-sitosterol contents (β-sitosterol, Δ-5-avenasterol, Δ-5-24-stigmastadienol, klerosterol, sitostanol) were between 92.96 and 94.63%. Varieties with the highest and lowest apparent β-sitosterol contents were oils which belong to Halhalı and Sarı Hasebi varieties respectively. β -sitosterol (83.08-88.21%), Δ-5-avenasterol (4.82-6.97%) and campesterol (2.28-3.43%) were identified as the main sterol components. Erythrodiol + uvaol contents of olive oils varied between 2.28 and 3.43% and these values were within the limits established by Turkish Food Codex.